On-going assessment of issues in the seaweed farming industry in Sabah, Malaysia - Datu Razali Datu Eranza; Arsiah Bahron; James Alin; Roslinah Mahmud; Siti Rahma Malusirang (Penerbit UMS, 2017)
This paper provides an insight on the issues in seaweed farming and industry in Semporna, Sabah. The paper reviewed previous work and recent publications that related to the issues in seaweed farming. Eleven issues identified and re-assessed by the authors as follows: (1) unavailability of good quality ‘seedlings’, (2) pollution in production areas, (3) occurrence of ‘ice-ice’ and epiphytes, (4) shortage of raw materials, (5) lack of capital to venture into the industry, (6) prolonged processing time in borrowing from financing institutions, (7) poor crop management, and (8) lack of fund for R&D programmes, (9) seaweed farming among Malaysian islanders and immigrants, (10) seaweed farmers and middlemen, and (11) seaweed quality and pricing. the data collection was done through series of fieldwork and telephone interview. The research questions were asked based on open-ended question/interview checklist. The result indicated that not all the 11 issues are affecting the seaweed industry, and the NKEA EPP3 programme does provide a positive impact in commercializing the seaweed industry of Malaysia.